2005
DOI: 10.1167/iovs.04-0715
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Aronia Extract on Rat Endotoxin-Induced Uveitis

Abstract: The results suggest that ACE has a dose-dependent anti-ocular inflammatory effect that is due to the direct blocking of the expression of the iNOS and COX-2 enzymes and leads to the suppression of the production of NO, PGE2, and TNF-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 55 publications
0
63
0
5
Order By: Relevance
“…14 Aronia crude extract exerted protective effects in LPS-stimulated RAW 264.7 cells and endotoxin-induced uveitis in rats by suppressing pro-inflammatory mediators such as iNOS and COX-2. 15,16 Recent studies have shown that A. melanocarpa fruit extract inhibits TNF-a-induced expression of adhesion molecules through suppression of NF-jB activation and reactive oxygen species (ROS) production in human aortic endothelial cells. 12 Although growing evidence suggested various disease-controlling activities of A. melanocarpa fruit, the modulatory activities of A. melanocarpa fruit on skin inflammation and its action mechanisms have not been fully determined.…”
Section: Introduction C Hronic and Dysregulated Inflammatory Responsesmentioning
confidence: 99%
“…14 Aronia crude extract exerted protective effects in LPS-stimulated RAW 264.7 cells and endotoxin-induced uveitis in rats by suppressing pro-inflammatory mediators such as iNOS and COX-2. 15,16 Recent studies have shown that A. melanocarpa fruit extract inhibits TNF-a-induced expression of adhesion molecules through suppression of NF-jB activation and reactive oxygen species (ROS) production in human aortic endothelial cells. 12 Although growing evidence suggested various disease-controlling activities of A. melanocarpa fruit, the modulatory activities of A. melanocarpa fruit on skin inflammation and its action mechanisms have not been fully determined.…”
Section: Introduction C Hronic and Dysregulated Inflammatory Responsesmentioning
confidence: 99%
“…Furthermore, their fruits are commonly used for the production of jams and jellies [11][12][13][14][15][16]. Black chokeberry, however, has been shown to be one of the most promising sources of phenolic phytochemicals with potential health benefits [17][18][19][20][21][22]. Owing to their exceptionally high contents of phenolic antioxidants, in particular anthocyanins, fruit juice concentrates of black chokeberries are increasingly used as natural colorants in industrial juice and nectar production.…”
Section: Introductionmentioning
confidence: 99%
“…For prevention of vision loss due to neuronal and vascular damage, topical or oral treatments with ocular penetration are ideal therapies that have been developed recently; in addition, several clinical studies have concentrated on the beneficial effects of natural polyphenols, such as resveratrol (17,18). Resveratrol is a plant-derived phytoalexin with diverse health benefits, including protection from metabolic disorders, such as diabetes (1921).…”
mentioning
confidence: 99%